2005
DOI: 10.1111/j.1365-3156.2004.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Field validation of sensitivity and specificity of rapid test for detection of Brugia malayi infection

Abstract: SummaryWe conducted a field study of a rapid test (Brugia Rapid) for detection of Brugia malayi infection to validate its sensitivity and specificity under operational conditions. Seven districts in the state of Sarawak, Malaysia, which are endemic for brugian filariasis, were used to determine the test sensitivity. Determination of specificity was performed in another state in Malaysia (Bachok, Kelantan) which is non-endemic for filariasis but endemic for soil-transmitted helminths. In Sarawak both the rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…This clearly entails that the traditional microscopic method failed to prove its reliability by providing with false negative results. A low density of mf in the system or prepatent infection can lead to CFA in the system but lack mf in the blood smear or any clinical symptoms [24], similar findings were reported with microscopic detections earlier [18], [30], [31]. This cryptic infection which is overlooked during field surveys [32], [33] and control of infection leads to the failure of MDA and eradication of filariasis.…”
Section: Discussionsupporting
confidence: 76%
“…This clearly entails that the traditional microscopic method failed to prove its reliability by providing with false negative results. A low density of mf in the system or prepatent infection can lead to CFA in the system but lack mf in the blood smear or any clinical symptoms [24], similar findings were reported with microscopic detections earlier [18], [30], [31]. This cryptic infection which is overlooked during field surveys [32], [33] and control of infection leads to the failure of MDA and eradication of filariasis.…”
Section: Discussionsupporting
confidence: 76%
“…Most immunodiagnostic research on filariasis has focused on the parasite stages that occur within the vertebrate host [32,33], and this work has produced sensitive and specific diagnostic tests for Bancroftian and brugian filariasis [5,34,35]. In contrast, few studies have examined antigen detection as a method for identifying and distinguishing LF parasites in mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be highly sensitive (>95%) and specific (≥ 99%) for detection of B. malayi and B. timori infections in laboratory evaluations [ 7 - 10 ] and field studies [ 11 - 14 ]. In a field study in Malaysia which is a low endemic area, Brugia Rapid detected about ten times more positive cases than parasitological diagnosis, while in the high endemic area of Indonesia, the increase in detection was about three times [ 11 , 12 ]. Follow-up post-treatment studies of mirofilaraemic individuals showed that the titres of IgG4 antibodies to Bm R1 decreased post-treatment.…”
Section: Resultsmentioning
confidence: 99%